Sale-Based vs Leased Based Contracts in House Financing Default - Anggari Kresnowati (Global Review of Islamic Economics and Business, 2022)
This study examines the relationship between FTV and house financing default, as well as the short and long-term effects on housing and apartment defaults. It also examines the extent to which Islamic banks implement suitable contracts for housing and apartment defaults, whether sale-based or lease-based. The data used in this paper is monthly time series data from 2015 to 2021. The finding of this study shows that the FTV policy in small houses and apartments (22-70 m2) positively significantly influences the house financing default in sale-based and lease-based contracts in both short and long-term periods. Moreover, the FTV policy in leased-based contracts has a significant influence on the house financing default in a big house (>70 m2) in a short-term period.